[Co@Sn6Sb6]3−: An Off‐Center Endohedral 12‐Vertex Cluster. Issue 47 (25th October 2018) - Wilson, Robert J.; Hastreiter, Florian; Reiter, Kevin; Büschelberger, Philipp; Wolf, Robert; Gschwind, Ruth M.; Weigend, Florian; Dehnen, Stefanie
Abstract: We report on the asymmetric occupation of a 12‐vertex cluster centered by a single metal atom. Three salts of related intermetalloid cluster anions, [Co@Sn6 Sb6 ] 3− (1 ), [Co2 @Sn5 Sb7 ] 3− (2 ), and [Ni2 @Sn7 Sb5 ] 3− (3 ) were synthesized, which have pseudo ‐ C 4 v ‐symmetric or pseudo ‐ D 4 h ‐symmetric 12‐vertex Sn/Sb shells and interstitial Co − ions or Ni atoms. Anion 1 is a very unusual single‐metal‐"centered" 12‐atom cluster, with the inner atom being clearly offset from the cluster center for energetic reasons. Quantum chemistry served to assign atom types to the atomic positions and relative stabilities of this cluster type. The studies indicate that the structures are strictly controlled by the total valence electron count—which is particularly variable in ternary intermetalloid cluster anions. Preliminary 119 Sn NMR studies in solution, supported by quantum‐chemical calculations of the shifts, illustrate the complexity regarding Sn:Sb distributions of such ternary systems. Abstract : Asymmetric occupation of a 12‐vertex cage was found in the new ternary intermetalloid cluster [Co@Sn6 Sb6 ] 3− (see picture). According to DFT calculations, the observed structure represents the global minimum for the given composition. Beside this cluster, a related one was identified with two interstitial cobalt atoms, [Co2 @Sn5 Sb7 ] 3−, as a minor component in the crystal structure, which was also confirmed by ESI mass spectrometry of a corresponding solution.